Stress Intervention Among University Students: Online Medical Tune Competition - Naing Oo Tha; Maher Fouad Sefein Beshay; Yeap, Boon Tat; Mohd Firdaus Mohd Hayati; Mohammad Saffree Jeffree (Penerbit UMS, 2022)
This innovative health intervention aimed to reduce stress among university students through interaction with music and developing awareness of the effect of music in stressful situations such as the current COVID-19 pandemic. The setting for this intervention was an online Instagram community with Universiti Malaysia Sabah (UMS) students as participants. For research, a cross-sectional observational health promotion design was used for this online health intervention, in conjunction with the Diffusion of Innovation Theory. The Medical Tune Competition was open to students from all university faculties. Process evaluation was done using the RE-AIM framework, while impact evaluation was conducted via a non-experimental post-test only design. A Google feedback form was distributed to the participating students, and descriptive analysis was performed using SPSS version 26. In total, 21 contestants participated whereby 85% of the feedback responses indicated that the programme had been enjoyable. All respondents were made aware that music could make them happy, and they stated that they would advise their friends or relatives to sing or enjoy music when stressed, 90.5% of the respondents felt music helped them relieve stress (4.43 ± 0.67), 85.7% believed that the Instagram platform was appropriate for this contest, and 14.3% suggested using Facebook or YouTube as a platform. The conclusion was that an online music competition held during the COVID-19 pandemic could be adopted and likely to be effective in raising awareness of music for stress management. In the future, innovators could develop and grow their own innovative e-health intervention programmes modelled on the Medical Tune initiative.